THE STUDENTS’ PERCEPTION ON TEACHERS’ BASIC TEACHING SKILLS IN ENGLISH CLASSROOM - Bestiara Bestiara; Arifmiboy Arifmiboy; Leli Lismay (Universitas Mahaputra Muhammad Yamin, 2021)
The research was conducted due to difference students’ perceptions on teacher basic teaching skills in English classroom at SMKN 1 Tanjung Raya. The design of this research was a survey research. Data were obtained through questionnaire using the likert scale. The sample was collected from 96 students at SMKN 1 Tanjung by using simple random sampling. Additionally, the analyzing of the data was done by identifying the respondent’s responses, analyzing the data and making a conclusion. The finding remarked that the students viewed teacher ability in explaining lesson was good with score 77.38%. It indicates the teachers mostly applied all the indicators of explaining skill in teaching and learning in the classroom. Furthermore, teacher ability to guide discussion skill was good enough with mean score is 73,37%. It assumed that during teaching and learning process, the teacher did a good enough to guide the discussion in the class.